Opportunistic screening for genital chlamydial infection. II: Prevalence among healthcare attenders, outcome, and evaluation of positive cases. Issue 1 (1st February 2003) - Pimenta, J M; Catchpole, M; Rogers, P A; Hopwood, J; Randall, S; Mallinson, H; Perkins, E; Jackson, N; Carlisle, C; Hewitt, G; Underhill, G; Gleave, T; et al.
Abstract : Objectives: To determine the prevalence and treatment outcomes among young women screened opportunistically for genital Chlamydia trachomatis and to evaluate the impact of screening in those participating. Design: An opportunistic screening programme (1 September 1999 to 31 August 2000) using urine samples, tested by ligase chain reaction (LCR). In-depth interviews were used for programme evaluation. Setting: Screening was offered in two health authorities at general practice, family planning, genitourinary medicine (GUM), adolescent sexual health, termination of pregnancy clinics and women's services in hospitals (antenatal, colposcopy, gynaecology and infertility clinics). Main participants: Sexually active women (16–24 years) attending for any reason. Main outcome measures: Screening data: prevalence of infection by age and healthcare setting; proportion of positive patients attending for treatment. Evaluation data: participants' attitudes and views towards screening and follow up. Results: In total, 16 930 women (16–24 years) were screened. Prevalence was higher in younger women (16–20) than those aged 21–24 years and was highly variable at different healthcare settings (range 3.4%–17.6%). Prevalence was approximately 9% in general practice. The role of the project health advisers in managing results and coordinating treatment of positive individuals was essential; the vast majority of all positives were known to be treated. Women felt that screening was beneficial. Improving awareness and education about sexually transmitted infections is required to alleviate negative reactions associated with testing positive for infection. Conclusions: Prevalence of infection outside GUM clinics is substantial and opportunistic screening using urine samples is an acceptable method of reaching individuals with infection who do not normally present at specialist clinics.